Acotaciones a una breve diálexis (Minerva, 2019)
The term diálexis, existent from the end of the first century, can denote a brief discourse, an essay, a short spoken piece dealing with a wide range of subjects or even an introductory part of a larger discourse. Many of the best Greek orators of the Second Sophistic made use of this pleasant genre. However, this rhetorical variation has not attracted the attention of present day scholars, since so few of them remain. Philostratus, in his Vitae Sophistarum, makes quite a few references to dialéxeis written by various sophists. It is very likely that he, too, favoured this rhetorical genre. We shall study a diálexis that was probably written and declaimed by the second Philostratus.